O olhar do pensamento complexo na infância: o fio de voz das professoras de crianças de zero a três anos a respeito da criatividade em tempos de pandemia da Covid-19 - Albuquerque, Débora Cristiana Alves Soares de (Universidade Federal do Tocantins, 2024)
This research, entitled “The look of Complex Thinking in childhood: the voice thread of teachers of children aged zero to three years old about creativity in times of the COVID-19 pandemic”, aims, in general, to analyze how teachers of children from zero to three years of age have noticed signs of creativity in their pedagogical practices, in the face of the Covid-19 pandemic scenario; specifically, it aims to know the perceptions of teachers regarding the concept of creativity, identify evidence of creativity in the pedagogical practices developed and demonstrate evidence that teachers build creative situations in times of pandemic. Thus, the following question arises: how have teachers of children from zero to three years old noticed signs of creativity in their pedagogical practices? For possible answers, the methodology used has a quantitative and qualitative approach, being a case study at the Municipal Center for Early Childhood Education Colar da Alegria, in the city of Dianópolis/TO, whose research subjects are the teachers, management team and children's mothers regularly enrolled in the 2021 school year. With theoretical foundations from Edgar Morin (2015) and Saturnino de La Torre (2005), among others, the Instrument for Valuing the Creative Development of Educational Institutions (VADECRIE) was applied, as well as an interview, in addition to direct observation techniques and document analysis. Once the analyzes were carried out, it was identified that the teachers' perceptions are close to the concept of creativity highlighted by Torre (2012b) and, through the answers to the questionnaire and the interviews, it was verified that there are signs of creativity in their pedagogical practices, Therefore, there are creative pedagogical practices at the Centro Municipal de Educação Infantil Colar da Alegria, highlighting the relevance of an education that values the child as a subject-protagonist of the learning process and, thus, stimulating their physical, affective, social and cognitive development